Strategi Pengembangan Usaha Budidaya Bawang Merah di Kabupaten Tabalong: The Development Strategy Onion Cultivation in Tabalong - Kusumayana, Purna; Redhanie, Ronna Vaty (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
The state of onion cultivation in the village is good enough, This village is economically advantageous to be developed and cultivated. From the results of calculations using SWOT analysis, then the values obtained from the analysis ofinternal factors (IFAS) by 2.80, then and for the value of the analysis of external factors (EFAS) by 2.76, meaning commodity onion has acomparative advantage the result is not only meet the needs of the region concerned but can be exported out of the territory Tabalong.The development strategy onion cultivation in Tabalong is aggressive strategy with more focus on SO strategy (Strength-Opportunities), by using force to take advantage of existing opportunities. Strategies (Strength-Opportunities): Develop and improve the image onion farming, develop agro-onion, optimizing groups for integrated pest management, improving the competence of the Human Resource, optimizing the coordination of relevant agencies, expanding markets for the products of onion.